Exploration of bluish violet‐emitting phosphor Ca3Al4ZnO10:Ti4+ with enhanced emission by Ca2+ vacancies. Issue 4 (20th September 2018) - Zhou, Zhi; Zhong, Yuan; Gu, Simin; Su, Yifeng; Xia, Mao; Zhang, Yongli; Zhou, Nan; Wang, Jing
Abstract: In this paper, we introduced a bluish violet‐emitting phosphor Ca3 Al4 ZnO10 :Ti (IV) (CAZO:Ti 4+ ) synthesized by high‐temperature solid‐state reaction. Upon 265 nm excitation, a broad emission band spanned from 300 nm to 500 nm and centered at 370 nm was observed. In addition, the effects of flux and charge compensation to photoluminescence properties of CAZO:Ti 4+ were systematically investigated. The results show that 103% improvement of emission intensity was achieved when 1% H3 BO3 flux was introduced and 32.8% enhancement of it for 2% Ca 2+ vacancies doped as charge compensator. Moreover, the lifetimes, band gap energy, concentration quenching mechanism, as well as electron transition process of CAZO:Ti 4+ were discussed. Due to the efficient broad bluish violet emission, this phosphor may find a potential application in mercury vapor‐excited fluorescent lamp for plant growth.